EFEKTIVITAS DAN EFISIENSI RETRIBUSI PARKIR KABUPATEN SUMBAWA - I Nyoman Sutama; U Usman; Vivin Fitryani; Evha Lista Sulyana (Pusat Riset dan Publikasi, 2020)
This study aims to know the effectiveness, efficiency and growth rate of parking retribution in Sumbawa District in 2015-2019. This study was a descriptive study with a quantitative approach. The data used was the number of parking retribution received in Sumbawa District 2015-2019 which was obtained from available documents. Data collection was done through documentation techniques. The data that has been collected were analyzed using the ratio analysis technique of effectiveness and efficiency and analysis of variants of revenue and costs. The findings of the study showed that parking retribution in Sumbawa District in 2015-2019 were less effective and inefficient. Based on results of the test showed that the effectiveness value of parking retribution was of 57.91% or was in the less effective category, while the efficiency value of parking retribution was of 139.98% or was in the inefficient category. The growth rate of parking retribution in Sumbawa District in 2015-2019 was of 109.16% or was in the positive category. This showed that the growth of parking retribution receipts in Sumbawa District in 2015-2019 can be said to be good.